JUNIOR HIGH SCHOOL STUDENTS’ CRITICAL THINKING SKILLS IN LEARNING PRISM CONCEPTS: Palembang, Indonesia - Ali Syahbana; Amrina Rizta; Nyimas Inda Kusumawati; Suryati (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to describe and analyze junior high school students’ critical thinking skills in learning prism concepts. A descriptive quantitative research design was employed, involving 109 students from three junior high schools in Palembang. Data were collected using a critical thinking skills test consisting of contextual mathematical problems developed based on Facione’s critical thinking indicators, interpretation, analysis, evaluation, and inference. The data were analyzed descriptively through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the overall level of students’ critical thinking skills in prism concept is categorized as low, with a mean score of 1,83. Among the indicators, interpretation obtained the highest score, whereas inference showed the lowest performance. In terms of gender differences, male students tended to perform better in the interpretation indicator, while female students demonstrated stronger abilities in analysis and evaluation. Nevertheless, both male and female students exhibited weaknesses in drawing valid conclusions and constructing logical mathematical arguments. These results suggest that mathematics instruction remains predominantly procedure-oriented and has not adequately fostered higher-order thinking skills. Therefore, mathematics learning should emphasize reasoning-based instruction, classroom discussion, and contextual problem-solving activities to comprehensively enhance students’ critical thinking skills. Keywords: critical thinking skills, prism, junior high school students